PERHITUNGAN FERTILITAS MENGGUNAKAN METODE ANAK KANDUNG: ANALISIS LANJUT DATA RISKESDAS 2013 - Lely Indrawati; Dwi Hapsari; Olwin Nainggolan (Populasi, 2016)
Total Fertility Rate (TFR) is the average number of children born alive by a number of women at the end of their reproductive period. TFR is one indicator of health development, especially maternal health in the country. Therefore, target of reducing the birth rate is still prioritized in RPJMN 2015-2019. Indirect method is more appropriate to calculate TFR, such as own-method children. Population of this study is women and their children in the same househoold with women of childbearing aged 15-49 years and children under five who live with their parents as sampling unit. Children under five in this analysis are the biological children while step children will be included in order to enhance the number children. The calculation based on 2013 Riskesdas (Riset Kesehatan Dasar) shows higher TFR compared to 2012 DHS (Demographic and Health Survey) which was 3.2 at national level. ASFR (Age Specific Fertility Rate) pattern shows highest fertility rate for age of 20-24, while it was second for age 15-19. The important implication is that family planning program has to concentrate on this age groups, such as by increasing age of the first marriage.